The effect of vitamin D replacement on spinal inhibitory pathways in women with chronic widespread pain - AKYÜZ, GÜLSEREN DERYA; GÜNDÜZ, OSMAN HAKAN; KENİŞ COŞKUN, ÖZGE (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Vitamin D replacement helps in pain reduction in patients with chronic widespread pain (CWP). But the current literature lack studies that investigate its mechanism. Cutaneous silent period (CSP) is the electrophysiologic analog of the spinal inhibitory pathways and an objective method to document their involvement. This study aims to show if vitamin D replacement has an effect on the spinal inhibitory pathways through CSP parameters. Female patients who have CWP with vitamin D deficiency were included. Patients received an 8-week replacement therapy of vitamin D. Patients' pain were evaluated using the visual analog scale (VAS) and Leeds assessment of neuropathic symptoms and signs pain scale (LANSS). Quality of life with Nottingham Health Profile (NHP) and CSP parameters were also recorded before and after treatment. A total of 51 patients were included in the final analyses. The mean age of the patients was 44.3 +/- 12.7 (minimum 18-maximum 65). Mean symptom duration was 13.1 +/- 6.7 (minimum3-maximum 24) months. Patients' mean BMI was 21.6 +/- 3.9 (minimum 18.0 maximum 29.1). Patients' median VAS and LANSS scores decreased significantly (p < 0.01) and NHP scores improved significantly in all subsets (p < 0.01). Vitamin D replacement did not significantly change CSP latency and duration (p = 0.06 and p = 0.12). Vitamin D replacement does not seem to work via modifying the spinal inhibitory pathways that are involved in the formation of the cutaneous silent period. This is the first study to objectively investigate the effect of vitamin D replacement on central sensitization mechanisms.
Keywords: Central sensitization; Chronic widespread pain; Cutaneous silent period; Pain; Vitamin D; QUALITY-OF-LIFE; MUSCULOSKELETAL PAIN; D SUPPLEMENTATION; NERVE-CONDUCTION; D DEFICIENCY; FIBROMYALGIA; PREVALENCE